Pengaruh Kinerja Perekonomian dalam Penanggulangan Kemiskinan: Perbandingan Antara Daerah Berbasis Pertambangan dan Daerah Perkotaan (Studi Kasus Kabupaten Tabalong dan Kota Banjarmasin) - Nur Rahmi; Syahrituah Siregar (PPJP Universitas Lambung Mangkurat, 2022)
The aim of this research is (1) determine the difference in the effect of Economic Performance (Economic Growth, Government Expenditure, Unemployment Rate and HDI) on poverty between Tabalong Regency and Banjarmasin City; (2) to analyze the factors that most influence poverty in each of Tabalong Regency and Banjarmasin City.This research is quantitative descriptive. The analytical method used is multiple linear regression analysis with dummy variables, and time series data. Dummy variables are used in this model as a differentiator characteristics of the region and the resources owned between each region. The variables used are economic growth, government spending, unemployment rate, HDI, dummy variables and poverty.The results showed that (1) Economic Growth, Government Expenditure, Unemployment Rate, and HDI simultaneously had a significant effect on Poverty in Tabalong Regency and Poverty in Banjarmasin City, and there are differences between poverty in Tabalong Regency and Banjarmasin City ; (2) The results of this study also indicate that government expenditure was the most dominant factor affecting poverty in Tabalong Regency and Banjarmasin City.